Measurement of browning of dehydrated candied papaya (Carica Papaya Linn.) during storage - Idea, Yvette Melissa S.; De Leon, Sonia Y. (1985)
The effects of humidity, storage temperature and sulfite on the color of dehydrated candied papaya were investigated. This was done by drying papaya treated sulfite and without sulfite (for the control) and then keeping these in storage at five different relative humidities (97.5, 88.8, 70.4, 47.2 and 18.8% RH) and at two storage temperature (10°C and 30°C). Browning was found to take place faster with increase in relative humidity and moisture content. The color of dehydrated candied papaya depended on the storage temperature and the presence of sulfite which protected against darkening at high storage temperature (30°C). At low temperature (10°C) the color of the sulfited product was not different from the control. Also, the color of the samples stored at low temperature did not change as much as those which were stored at high temperature (30°C).
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Papaya -- Philippines; Papaya, Candied